A semantic study on figurative languages used in thailand advertisements - Pramusita, Santa Maya; Putri, Daiya ((JELE) Journal Of English Language and Education, 2018)
Advertisement is one of communication tools used to promote products, influence people to do something, and plant certain ideologies. In achieving these goals, the use of figurative language is deeply needed due to its effectiveness in creating enchanting campaigns. In this paper, a semantic study is done to analyze the figurative languages and its contextual meanings in four Thailand advertisements, with the hope that it can give an explanation of how messages delievered through the advertisements. As for the advertisements that the writers use are Smooth E. Baby Face Foam, Smooth E. Face Scrub Advertisement Series, Peppermint Field Inhaler, as well as Nature Gift 21, and Coffee Plus Advertisement that have interesting plots and many figurative languages. The result of this study shows that hyperbole and simile are the most figurative languages found in those advertisements, which is used to insert some humors and attract audiences’ attention to buy the products.